LAYANAN KESEHATAN DAN PENINGKATAN KETERAMPILAN WIRAUSAHA JAMUR TIRAM KELOMPOK ANAK-ANAK TUNANETRA YPAB SUKOLILO - Pratiwi Soesilawati; R. Darmawan Setijanto (Jurnal Layanan Masyarakat (Journal of Public Services), 2017)
Healthy living as defined by the World Health Organization (WHO) is a prosperous state of body, soul, and social, so that one lives productively socially and economically. Yayasan Pendidikan Anak Buta (YPAB) Surabaya houses dormitories and schools of Kindergarten, elementary, junior and senior high schools. Blind school students are community groups that still require health and economic assistance. The cost of living for students in dormitories and schools of the blind is largely sustained by donors. Only a small proportion of students come from middle-income families and are able to pay tuition and living expenses, so the burden of the foundation to provide education and living expenses is very heavy. For that the Community Service Team of Faculty of Dentistry Airlangga University to design assistance activities in the form of health services and appropriate technology training. The purpose of this activity is to improve the health status of blind students and prepare blind students to be economically productive through the accompaniment of oyster mushroom entrepreneur. The specific target of this activity is to instill clean healthy living habits to students and train students involved in the production and marketing management of oyster mushrooms as the appropriate technology for the provision of life in the future. The solution used is public health services through the establishment of School Health Enterprises in collaboration with doctors from health care centers in this case Airlangga University Education Hospital for eye health services, general health, children’s health and dental health. Increased economic productivity is done through the training of oyster mushroom entrepreneur, oyster mushroom processing and marketing management of oyster mushroom and its processed products. At the end of the activity, students have basic knowledge of hygiene and health to maintain health and have soft skill entrepreneur of oyster mushroom as stock of life  AbstrakHidup sehat seperti yang dideﬁnisikan oleh World Health Organization (WHO) adalah keadaan sejahtera dari badan, jiwa, dan social, sehingga seseorang hidup produktif secara sosial dan ekonomi. Yayasan Pendidikan Anak Buta Surabaya menaungi asrama dan sekolah Taman Kanak-Kanak, SD, SMP dan SMA. Siswa sekolah tunanetra adalah kelompok masyarakat yang masih memerlukan pendampingan kesehatan dan ekonomi. Biaya hidup siswa selama di asrama dan sekolah tunanetra sebagian besar ditopang oleh donatur. Hanya sebagian kecil siswa yang berasal dari keluarga ekonomi menengah dan mampu membayar uang sekolah serta biaya hidup, sehingga beban yayasan untuk menyelenggarakan pendidikan dan biaya hidup sehari-hari sangat berat. Untuk itu Tim Pengabdian Masyarakat Fakultas Kedokteran Gigi Universitas Airlangga merancang kegiatan pendampingan dalam bentuk layanan kesehatan dan pelatihan teknologi tepat guna. Tujuan kegiatan ini adalah meningkatkan derajat kesehatan siswa tunanetra dan mempersiapkan siswa tunanetra menjadi insan yang produktif secara ekonomi melalui pendampingan wirausaha jamur tiram. Target khusus dari kegiatan ini adalah menanamkan kebiasaan hidup bersih sehat kepada siswa dan melatih siswa terlibat dalam produksi dan manajemen pemasaran jamur tiram sebagai teknologi tepat guna untuk bekal hidup di kemudian hari. Solusi yang digunakan adalah layanan kesehatan umum melalui rintisan pembentukan Usaha Kesehatan Sekolah bekerjasama dengan dokter dari pusat pelayanan kesehatan dalam hal ini Rumah Sakit Pendidikan Universitas Airlangga untuk pelayanan kesehatan mata, kesehatan umum, kesehatan anak dan kesehatan gigi. Peningkatan produktiﬁtas ekonomi dilakukan melalui pelatihan wirausaha jamur tiram, praktik pengolahan jamur tiram dan manajemen pemasaran jamur tiram beserta hasil olahannya. Pada akhir kegiatan, siswa memiliki dasar pengetahuan kebersihan dan kesehatan untuk memelihara kesehatan dan memiliki soft skill wirausaha jamur tiram sebagai bekal hidup